2020
DOI: 10.7759/cureus.10525
|View full text |Cite
|
Sign up to set email alerts
|

Sunitinib or Pazopanib: Is There Any Difference Between Tyrosine Kinase Inhibitors in the Pre-Nivolumab Setting in Metastatic Renal Cell Carcinoma?

Abstract: Introduction Treatment options for metastatic renal cell carcinoma disease have been improved in recent years. However, there is still no optimal treatment sequence or combination for metastatic disease. We aimed to investigate whether patients differed in terms of disease outcomes regarding pre-nivolumab tyrosine kinase inhibitors (TKIs). Material and methods The analysis of patients was performed after all cohorts were sub-grouped into two groups according to pre-nivolumab TKIs as following the sunitinib arm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…However, no recommendation has been made regarding the use of sunitinib versus pazopanib in first-line settings. Furthermore, the treatment paradigm for metastatic RCC has recently changed with the introduction of immune checkpoint inhibitors (ICI) in combination with VEGFR-TKIs [ 4 , 13 , 14 ], but the percentage of patients responding to this novel therapeutic strategy remains unsatisfactory (~10%) [ 15 , 16 , 17 ]. There are still no optimized guidelines for TKIs selection in these combination regimens to achieve the optimal response with minimum toxicity [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no recommendation has been made regarding the use of sunitinib versus pazopanib in first-line settings. Furthermore, the treatment paradigm for metastatic RCC has recently changed with the introduction of immune checkpoint inhibitors (ICI) in combination with VEGFR-TKIs [ 4 , 13 , 14 ], but the percentage of patients responding to this novel therapeutic strategy remains unsatisfactory (~10%) [ 15 , 16 , 17 ]. There are still no optimized guidelines for TKIs selection in these combination regimens to achieve the optimal response with minimum toxicity [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the treatment paradigm for metastatic RCC has recently changed with the introduction of immune checkpoint inhibitors (ICI) in combination with VEGFR-TKIs [ 4 , 13 , 14 ], but the percentage of patients responding to this novel therapeutic strategy remains unsatisfactory (~10%) [ 15 , 16 , 17 ]. There are still no optimized guidelines for TKIs selection in these combination regimens to achieve the optimal response with minimum toxicity [ 15 ]. Thus, the identification of markers able to predict the efficacy and toxicity of these targeted drugs may overcome these issues, allowing the selection of the best therapeutic option for each patient.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, sunitinib and pazopanib were among the most frequently adopted TKI in mRCC which inhibit VEGF and VEGFR and had similar efficacies. [47][48][49][50] IC 50 of organoid growth was higher than the clinically relevant concentration (i.e., peak plasma concentration) of sunitinib (200 nM). 51 Therefore, the organoids were considered as sunitinib-resistance in clinical setup though the patient received pazopanib.…”
Section: Discussionmentioning
confidence: 87%
“…We demonstrated that our RCC organoid model could potentially serve as a platform in choosing suitable drug interventions for patients and we sought to provide correlations between our in vitro results and clinical observations. In fact, sunitinib and pazopanib were among the most frequently adopted TKI in mRCC which inhibit VEGF and VEGFR and had similar efficacies 47–50 . IC 50 of organoid growth was higher than the clinically relevant concentration (i.e., peak plasma concentration) of sunitinib (200 nM) 51 .…”
Section: Discussionmentioning
confidence: 99%
“…These agents have important advantages, including low toxicity and high specificity, and can be used in combination with other therapeutic agents [ 9 ]. Among the various approved TKIs, sunitinib and pazopanib are widely preferred as first-line treatments for metastatic ccRCC (mRCC) [ 3 , 10 ]. Sunitinib is an orally administered TKI with antitumor and anti-angiogenic activity.…”
Section: Introductionmentioning
confidence: 99%